Spiropiperidines. I. Synthesis of 1'-Substituted Spiro [4H-3, 1-benzoxazine-4, 4'-piperidin]-2 (1H)-one Derivatives and Evaluation of Their Antihypertensive Activity - TAKAI, HARUKI; SHUTO, KATSUICHI; TERANISHI, MASAYUKI; KUBO, KAZUHIRO; KASUYA, YUTAKA; KARASHIMA, NAOKO; OBASE, HIROYUKI; SHIGENOBU, KOKI; KARASAWA, AKIRA; HASHIKAMI, MAKIKO (Chemical & pharmaceutical bulletin, 1985)
General synthetic methods for the preparation of 4-(2-aminophenyl)-4-hydroxypiperidine derivatives have been developed. The application use of these derivatives in the synthesis of 1'-substituted spiro [4H-3, 1-benzoxazine-4, 4'-piperidin]-2 (1H)-one derivatives is described, and the antihypertensive activity of the products is also reported.